Effects of urbanization on carabid beetles in an urban riparian area. Issue 6 (17th June 2022) - Do, Yuno; Choi, Moon Bo
Abstract: Urban rivers and riparian areas serve as corridors that move matter, organisms, and energy to urban areas from adjacent landscapes. However, anthropogenic disturbances and obstructions in river basins have severely impeded the function of many urban rivers as ecological corridors. Here, we used carabid beetles to assess the impact of urbanization on a river and its riparian areas. We identified carabid diversity and composition along an urbanization gradient. We classified 1, 855 individuals in 17 species along a river. The carabid communities in riparian areas reflected critically disturbed habitats, and their composition markedly differed between the riparian areas and their adjacent habitats. Carabid beetle diversity sharply decreased with increasing urbanization. Flight capacity and feeding type varied along the urbanization gradient. Environmental variables associated with urbanization such as riparian quality and disturbance level significantly influenced carabid diversity. Land use type in increasingly urbanized areas was correlated with decreased carabid diversity and increased carabid dominance. Patch density, patch size, and interspersion metrics revealed that fragmentation and isolation influenced carabid diversity. Mitigation of disturbances and conservation of riparian microhabitats are required to improve biodiversity in riparian areas.